2017
DOI: 10.1039/c7cy00587c
|View full text |Cite
|
Sign up to set email alerts
|

Tripodal amine ligands for accelerating Cu-catalyzed azide–alkyne cycloaddition: efficiency and stability against oxidation and dissociation

Abstract: Ancillary ligands, especially the tripodal ligands such as tris(triazolylmethyl)amines, have been widely used to accelerate the Cu-catalyzed azide-alkyne cycloaddition (CuAAC, a “click” reaction). However, the relationship between the activity of these Cu(I) complexes and their stability against air oxidation and ligand dissociation/exchange was seldom studied, which is critical for the applications of CuAAC in many biological systems. In this work, we synthesized twenty-one Cu(I) tripodal ligands varying in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Moreover, it was previously reported that the addition of only 2 equivalents of GSH was sufficient to inhibit the catalytic activity of common tris(triazole)-based CuAAC catalysts. 64 This behaviour also highlights the benefits of the hemicryptophane flexibility–rigidity balance, since Cu-catalysts encapsulated in azacryptand caged ligands were found to be too structurally flexible to efficiently prevent the GSH-induced deactivation of the confined catalysts. 65…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, it was previously reported that the addition of only 2 equivalents of GSH was sufficient to inhibit the catalytic activity of common tris(triazole)-based CuAAC catalysts. 64 This behaviour also highlights the benefits of the hemicryptophane flexibility–rigidity balance, since Cu-catalysts encapsulated in azacryptand caged ligands were found to be too structurally flexible to efficiently prevent the GSH-induced deactivation of the confined catalysts. 65…”
Section: Discussionmentioning
confidence: 93%
“…The use of accelerating ligands (e. g., tris-hydroxypropyltriazolylmethylamine, THPTA) in Cucatalysed azide-alkyne cycloaddition (CuAAC) to increase the kinetics and the conversion in case of slow reactions has been described. [19] As the use of metal catalyst could represent a problem from both a biological and an environmental point of view, strained cyclooctynes have been studied as starting materials to overcome the issues associated with the use of metal catalysts, in the so-called strain-promoted azide-alkyne cycloaddition (SPAAC) reactions. [20,21] Due to the intramolecular strain, the cyclooctyne reacts readily with azide without metal catalyst at ambient temperature affording high yields of triazole product.…”
Section: Reactions Involving Azidesmentioning
confidence: 99%
“…296 Furthermore, by stabilizing the Cu I species, the ligands accelerate the reaction. 297,298 A selection of reported reaction conditions can be found in ESI † Tables S5 and S6.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%